PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN LIFT THE FLAP BOOK BAGI GURU TK - Rommel Sinaga; Ika Agustina; Murtopo Murtopo; Syahripal Putra (Indonesian Collaboration Journal of Community Services, 2023)
This Community Service is impelled by the urgency of developing the competency of kindergarten teachers to design reading learning media for early childhood so that learning is more interesting and triggers children to quickly master language skills. The problems that occur are due to a lack of training to improve the skills and competence of teachers to prohibit children from reading performances with the weak ability of students to read and spell. From the track record of the initial survey conducted by the service team, the objective of this service activity is to rectify teachers' competency to use children's reading media through training on designing Lift the Flap Book media at TK Al-Fajar Medan. Meanwhile, the specific target planned is the formation of a Kindergarten Teacher Consultation Community which accommodates Kindergarten teachers as a place to improve skills in transferring knowledge to other teachers. The method that will be used to provide solutions to partner problems is by means of training through the 3 programs namely Initial Test, Training, and Peer Teaching. The initial test is the initial process of implementing community service classifying at what level the competence and skills of the community service program participants. After taking part in the Test program, participants take part in a Training program where participants teach skills in designing Lift the Flap Book media. Third, participants take part in Peer Teaching to provide practical experience in properly implementing the teaching process with Lift the Flap Book media. From the outcome of the community service, it is recognized that there is a notable raise in the competency of the trainees in designing learning media, especially in the animal and plant sub-material through the media creation of the Lift the Flap Book